Designing a novel photoinduced electron transfer-based small-molecule fluorescent probe specific for CYP3A isozymes. (1st September 2021) - Fujimoto, Keiichi; Takeuchi, Hayato; Takaku, Tomoyuki; Abe, Jun; Harada, Koichiro
Graphical abstract: Abstract: Cytochrome P450 (CYPs) are oxidoreductases distributed in various tissues in plants and animals. Among the CYP families, CYP3A is the most abundant in vivo, particularly in humans, and it is involved in the metabolism of many drugs. It is crucial to measure CYP3A activity for both pharmaceuticals and agrochemicals because inhibition or induction of this enzyme can seriously affect the occurrence of toxicity or efficacy. In the present study, a novel fluorescent probe, 6-(2, 5-bis(trifluoromethyl)benzyloxy)-9-(4-methoxy-2-methylphenyl)-3 H -xanthen-3-one (BMX, quantum efficiency: 21%), was designed and synthesized. The design was done by photoinduced electron transfer strategy. BMX was specifically metabolized only using CYP3A to generate 2-Me-4-MeO TokyoGreen (quantum efficiency: 85%), resulting in strong fluorescence in the presence of CYP3A isozymes. Protein assays using recombinant human, rat, and mouse CYP isozymes demonstrated the selective metabolism of BMX and production of fluorescence only by CYP3A in all species.